Changes in plasma membrane Ca-ATPase and stromal interacting molecule 1 expression levels for Ca(2+) signaling in dystrophic mdx mouse muscle. - Cully, Tanya R.; Edwards, Joshua N.; Friedrich, Oliver; Stephenson, D. George; Murphy, Robyn M; Launikonis, Bradley S. (American journal of physiology. Cell physiology, 2012)
The majority of the skeletal muscle plasma membrane is internalized as part of the tubular (t-) system, forming a standing junction with the sarcoplasmic reticulum (SR) membrane throughout the muscle fiber. This arrangement facilitates not only a rapid and large release of Ca(2+) from the SR for contraction upon excitation of the fiber, but has also direct implications for other interdependent cellular regulators of Ca(2+). The t-system plasma membrane Ca-ATPase (PMCA) and store-operated Ca(2+) entry (SOCE) can also be activated upon release of SR Ca(2+). In muscle, the SR Ca(2+) sensor responsible for rapidly activated SOCE appears to be the stromal interacting molecule 1L (STIM1L) isoform of STIM1 protein, which directly interacts with the Orai1 Ca(2+) channel in the t-system. The common isoform of STIM1 is STIM1S, and it has been shown that STIM1 together with Orai1 in a complex with the partner protein of STIM (POST) reduces the activity of the PMCA. We have previously shown that Orai1 and STIM1 are upregulated in dystrophic mdx mouse muscle, and here we show that STIM1L and PMCA are also upregulated in mdx muscle. Moreover, we show that the ratios of STIM1L to STIM1S in wild-type (WT) and mdx muscle are not different. We also show a greater store-dependent Ca(2+) influx in mdx compared with WT muscle for similar levels of SR Ca(2+) release while normal activation and deactivation properties were maintained. Interestingly, the fiber-averaged ability of WT and mdx muscle to extrude Ca(2+) via PMCA was found to be the same despite differences in PMCA densities. This suggests that there is a close relationship among PMCA, STIM1L, STIM1S, Orai1, and also POST expression in mdx muscle to maintain the same Ca(2+) extrusion properties as in the WT muscle.